Strength Defined By Speed and Its Relationship with Dribbling Speed in Futsal Players - Khudair , Naseer (Journal of Physical Education, 2011)
Research ( 5 Parts ) Part (1) It Contained the introduction and its importance to stress that the basketball player must have the ability of speed endurance which help the players to continue the performance in keeping their speed and delaying the appearance of tired . In other hand the player must have agility element which is good in many stations because he needs to join many skills motor in the same time . this part included also the problem of the research that declare the level of the players is coming down and they became tired early this will make their agility weak during the games to be inverted in the negative in agility .The researcher meaned to put special trainings to speed endurance for two distances (12m , 24m ) and to know their effects to develop the speed endurance and agility element and which is the best distance. Part (2) It contained theoretical studies . It included the importance of speed endurance and agility in basketball game . Part (3) This part contained the research methodology and procedures . the researcher used experimental method to two groups design . Part (4) A section view the results , analysis and discussion of the variable under study and which has been reached to achieve the objectives of the research and verification of the hypotheses . Part (5) Conclusions and recommendations . The findings contained the following :- 1- The specialty training for distances (12m , 24m) which were prepared from the researcher to lead to develop the speed endurance and agility element . 2- The specialty training of the distance (24m) realized rate of develop more than the rate of develop the distance (12m) in the speed endurance test there weren’t any differences between the two groups in the post test 3- The group of the distance (12m) achieved a best results than the group of distance (24m)in the agility test . 4- The using of the similar and approach distances in the real performance in the activity were their effects to develop the players for the best during the Training in a high intensity in a short time . The recommendations :- 1- Emphasize of using the two distance (12 , 24m) to develop the speed endurance and can focus at distance (24m) . 2- Emphasize of using the distance (12m) to develop the agility . 3- Making a similar researches for other activities or different ages types .